Economics of resources, agriculture, and food - Seitz, Wesley D. (McGraw-Hill, 2002)
This text is intended for students who are interested in learning the principles of economics. It is particularly appropriate for students enrolled in colleges of agriculture and in some of the biological and physical science courses in liberal arts colleges, where a familiarity of agriculture will help enliven examples. Economics of Resources, Agriculture, and Food was developed to present the full range of basic economic theory, which is illustrated with examples from resource, agricultural, and food issues of today. Students who study this text will be prepared to understand the basis for most economic and management decisions.